STUDENTS’ EXPERIENCES OF PASSIVE ENGLISH LANGUAGE EXPOSURE THROUGH SOCIAL MEDIA: AN EXPLORATORY STUDY IN AN INDONESIAN EFL CONTEXT - Angel Amori Angel Amori; Ferri Susanto; Endang Haryanto (JIBS : JURNAL ILMIAH BAHASA DAN SASTRA, 2026)
The growing use of social media has created new opportunities for English exposure outside formal classroom settings. Students can encounter English naturally through videos, captions, music, and other digital content without intentionally learning the language. This study explores the experiences of eighth-semester students in encountering passive English exposure through social media and identifies its benefits and challenges. A qualitative exploratory design was used involving eight students from the English Education Department at Universitas Islam Negeri Fatmawati Sukarno Bengkulu. Data were collected through observation, interviews, and documentation, and analyzed using the Miles, Huberman, and Saldaña interactive model. The findings show that passive English exposure occurred naturally through YouTube, TikTok, and Instagram during entertainment and daily activities. The exposure included audiovisual, audio, and textual input such as videos, captions, subtitles, comments, music, and memes. Repeated exposure supported incidental learning of vocabulary, slang, expressions, pronunciation, and language patterns. Social media also functioned as an informal and flexible learning space through algorithmic recommendations and personal interests. However, students faced difficulties such as unfamiliar vocabulary, fast speech, slang, and non-standard English. To overcome these challenges, they used contextual clues, visual support, translation tools, and repeated viewing. Overall, passive exposure through social media provides meaningful informal English learning experiences beyond the classroom.